2007
DOI: 10.2337/db06-1033
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of GLP-1 and GIP Receptor Expression by Hyperglycemia

Abstract: Stimulation of insulin secretion by the incretin hormones glucagon-like peptide 1 (GLP-1) and glucose-dependent insulinotropic peptide (GIP) has been found to be diminished in type 2 diabetes. We hypothesized that this impairment is due to a defect at the receptor level induced by the diabetic state, particularly hyperglycemia. Gene expression of incretin receptors, GLP-1R and GIPR, were significantly decreased in islets of 90% pancreatectomized (Px) hyperglycemic rats, with recovery when glucose levels were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
220
3
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 331 publications
(248 citation statements)
references
References 47 publications
14
220
3
6
Order By: Relevance
“…Finally, our mRNA expression studies suggest altered incretin signalling in ZF-Px islets, since the expression of Glp1r, Gipr and Ffral1 (also known as Gpr40) was reduced. Reduced mRNA expression and protein content of the GLP-1 receptor has been observed in islets of ZDF and 90% pancreatectomised diabetic rats [44]. Altered incretin signalling is thought to contribute to beta cell dysfunction and the current data are consistent with this view, at least with respect to the in vivo situation.…”
Section: Sg Autophagysupporting
confidence: 78%
“…Finally, our mRNA expression studies suggest altered incretin signalling in ZF-Px islets, since the expression of Glp1r, Gipr and Ffral1 (also known as Gpr40) was reduced. Reduced mRNA expression and protein content of the GLP-1 receptor has been observed in islets of ZDF and 90% pancreatectomised diabetic rats [44]. Altered incretin signalling is thought to contribute to beta cell dysfunction and the current data are consistent with this view, at least with respect to the in vivo situation.…”
Section: Sg Autophagysupporting
confidence: 78%
“…One possible explanation for the decrease in exenatide-induced insulin release during 7-day culture with elevated glucose is downregulation of the GLP-1 receptors on beta cells [45]. Furthermore, 7-day exenatide-treated islets had comparable basal insulin release but a greater insulin response to elevated glucose following incubation in exenatide-free buffer and had a higher insulin content.…”
Section: Discussionmentioning
confidence: 98%
“…It has been demonstrated that the effect of GIP in stimulating insulin secretion is impaired in type 2 diabetes (Vilsboll et al, 2002). The reason for this has recently been suggested to be secondary to hyperglycemia as demonstrated experimentally both in vivo (Xu et al, 2007) and in vitro (Zhou et al, 2007).…”
Section: Gip Receptorsmentioning
confidence: 98%